COVID-19 and Diabetic Nephropathy - Maremonti, Francesca; Locke, Sophie; Tonnus, Wulf; Beer, Kristina; Brucker, Anne; Gonzalez, Nadia Zamora; Latk, Marcus; Belavgeni, Alexia; Hoppenz, Paul; Hugo, Christian; Linkermann, Andreas (Hormone and Metabolic Research, 2022)
Diabetic nephropathy is the most common condition that requires a chronic renal replacement therapy, such as hemodialysis, peritoneal dialysis, kidney transplantation, or simultaneous kidney-pancreas transplantation. Chronic kidney disease progression, that is the loss of nephrons, which causes the continuous decline of the eGFR, underlies the pathogenesis of diabetic nephropathy. During the COVID-19 pandemic, it became clear that diabetic nephropathy is amongst the independent risk factors that predicts unfavourable outcome upon SARS-CoV2 infection. While we still lack conclusive mechanistic insights into how nephrons are rapidly lost upon SARS-CoV2 infection and why patients with diabetic nephropathy are more susceptible to severe outcomes upon SARS-CoV2 infection, here, we discuss several aspects of the interface of COVID-19 with diabetic nephropathy. We identify the shortage of reliable rodent models of diabetic nephropathy, limited treatment options for human diabetic nephropathy and the lack of knowledge about virus-induced signalling pathways of regulated necrosis, such as necroptosis, as key factors that explain our failure to understand this system. Finally, we focus on immunosuppressed patients and discuss vaccination efficacy in these and diabetic patients. We conclude that more basic science and mechanistic understanding will be required both in diabetic nephropathy as well as in host immune responses to the SARS-CoV2 virus if novel therapeutic strategies are desired.
Keywords: diabetic nephropathy; diabetes; chronic kidney disease; COVID19; necroptosis